Avaliando impactos econômicos do programa “Reflorestar” de pagamentos por serviços ambientais - Renato Nunes de Lima Seixas; Pablo Medeiros Jabor (Revista de Economia Mackenzie)
This article aims to estimate the economic impacts of the “Reflorestar” pro-gram for payments for environmental services implemented in the state of Espíri-to Santo in 2014. To estimate the causal effect of the program, we use a differen-ces-in-differences strategy that explores the gradual adherence of the program in municipalities. Impacts on municipal GDP, value added in agriculture, industry, services, and public administration, planted area, and employment were estima-ted. The results show limited effects on aggregate indicators of municipal econo-mic activity. When analyzing heterogeneous impacts by municipality size and crop type, we find an increase in total agricultural production and coffee produc-tion in municipalities with lower per capita GDP and a reduction in corn produc-tion in municipalities with higher per capita GDP. These results suggest a substi-tution of temporary crops for preservation areas, which can be quickly reconverted at the end of the payments for environmental services contracts.